1982
DOI: 10.1007/bf00987781
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of oviposition by volatiles of certain plants and chemicals in the leafhopperAmrasca devastons (distant)

Abstract: Oviposition by the leafhopperAmrasca devastans (Distant) on its susceptible host plant, cotton (Gossypium hirsutum var. PS-10), was inhibited by the volatiles of certain plants and by the vapors of some chemicals occurring in various plants when these were presented at a distance from the ovipositional substrate. The effectiveness of the volatiles of the plants for inhibiting the oviposition decreased in the order: eucalyptus > coriander=castor=tomato > lime,Ocimum being without effect. Among the volatile plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

1984
1984
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 10 publications
1
14
0
Order By: Relevance
“…These compounds are common acyclic monoterpenes playing roles in plant-insect interaction, and their repellent effect on mosquitoes is well known (Kaufman et al 2010;Montefuscoli et al 2014). Their potential effect on agronomic insect pests remain, however, largely unexplored (Lee et al 1997;Saxena and Basit 1982), but essential oils containing these compound show some efficiency (Costa et al 2015;Olivero-Verbel et al 2010), and our results suggest they have potential also against D. radicum in the field.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…These compounds are common acyclic monoterpenes playing roles in plant-insect interaction, and their repellent effect on mosquitoes is well known (Kaufman et al 2010;Montefuscoli et al 2014). Their potential effect on agronomic insect pests remain, however, largely unexplored (Lee et al 1997;Saxena and Basit 1982), but essential oils containing these compound show some efficiency (Costa et al 2015;Olivero-Verbel et al 2010), and our results suggest they have potential also against D. radicum in the field.…”
Section: Discussionmentioning
confidence: 63%
“…This bicyclic monoterpene, commonly found in plants of the Myrtacea family, plays a major role in plant-microorganism (Steeghs et al 2004) and plant-insect interactions (Schiestl and Roubik 2003). It has been tested against mosquitoes (Klocke et al 1987) and on a great variety of insect pests for its toxicity, repellency or its effect on oviposition (Bekele and Hassanali 2001;Karemu et al 2013;Koul et al 2013;Li et al 2007;ObengOfori et al 1997;Saxena and Basit 1982), revealing highly contrasted results depending on the biological model, but was identified to reduce D. radicum oviposition by 75 % in laboratory conditions (den Ouden et al 1996). Raw products containing eucalyptol, such as essential oils or eucalyptus leaves, have also been studied for pest management (Batish et al 2008;Santos 2006).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Neral has been reported to have an oviposition deterrent effect on the leafhopper, Amrasca devastans (Distant.) (Saxena and Basit 1982).…”
Section: Effect Of Lso On Oviposition and Egg Hatchmentioning
confidence: 95%
“…The chemical composition of essential oils from Equisetum ramossisemum (In press) revealed that the oils contain a high content of monoterpenoids and sesquiterpenoids as compared to the oils of other Equisetums (Saxena and Basit, 1982). Various toxicities have been ascribed to oils that contain terpenes (Gordon et al, 1982).…”
Section: Introductionmentioning
confidence: 99%